Economic Value Added (EVA) dan Market Value Added (MVA) - Gustita Arnawati Putri; Retno Wilis Tito Atmojo; Sari Widati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
This research is an empirical study to analyze the data causally (cause and effect). The aim of this study was to determine the performance of manufacturing firms sector industry consumption in indonesia stock exchange. In addition, this study also aimed to determine the influence Economic Value Added (EVA), Return on Asset (ROA), Return on Equity (ROE), Debt Ratio (DR) and Degree of Operating Leverage (DOL) to the Market Value Added (MVA). Population in this research are manufacturing companies sector industry consumption that listing on Indonesia Stock Exchange. Determination of the sample is done by purposive sampling method. Period of research is 5 years during 2013 until 2017. By analysis of data using multiple regression showed that the results showed only a Return on Asset (ROA), Return on Equity (ROE), Debt Ratio (DR) and Degree Of Operating Leverage (DOL) which has positive against Market Value Added, while Economic Value Added (EVA) and Earning Per Share (EPS) does not affect the Market Value Added